2020
DOI: 10.1111/pan.13994
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of low‐flow anesthesia at a tertiary pediatric center: A quality improvement initiative

Abstract: Inhaled anesthetics represent significant drug costs for anesthesia care, and previously, there have been limited or unreliable ways to measure the efficient use of anesthetics. In addition, the negative environmental impact of volatile anesthetics is a growing concern, so there is an increased focus on responsibly delivering an anesthetic. Low-flow anesthesia has gained popularity due to recent advances in anesthesia machines and CO 2 absorbents, which allow anesthesiologists to use low-flow anesthesia and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 6 publications
0
26
0
1
Order By: Relevance
“… Using low fresh gas flow or closed-circuit delivery can reduce the volume of volatile gas consumed by 20%. 45 , 50 , 51 New technologies, such as Dynamic Gas Scavenging Systems or silica zeolite, can absorb, destroy, and even recycle anaesthetic waste gases. 52 , 53 , 54 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Using low fresh gas flow or closed-circuit delivery can reduce the volume of volatile gas consumed by 20%. 45 , 50 , 51 New technologies, such as Dynamic Gas Scavenging Systems or silica zeolite, can absorb, destroy, and even recycle anaesthetic waste gases. 52 , 53 , 54 …”
Section: Resultsmentioning
confidence: 99%
“…Using low fresh gas flow or closed-circuit delivery can reduce the volume of volatile gas consumed by 20%. 45 , 50 , 51 …”
Section: Resultsmentioning
confidence: 99%
“…This could have the additional benefit of reducing the financial cost of anaesthesia, although the purchase of new breathing systems and increased use of soda‐lime would need to be included in any calculations. These reductions are slightly greater than 25% reduction in sevoflurane usage achieved in human paediatric anaesthesia through a quality improvement initiative (Glenski & Levine 2020) and the 21% reduction in isoflurane using an inhalational anaesthetic computer simulation (Feldman 2012). However, it should be noted both these studies involved reduction of fresh gas flow in circle systems to 1 l/min from a standard of 2 l/min rather than a shift from non‐rebreathing systems to low‐flow techniques (Feldman 2012, Glenski & Levine 2020).…”
Section: Discussionmentioning
confidence: 85%
“… 14 , 15 In numerous studies carried out with high-flow anesthesia, it has been demonstrated that anesthetic gas and oxygen consumption was significantly higher compared to low-flow anesthesia. 16 , 17 Tissues exposed to high oxygen produce reactive oxygen. Oxidative cell damage often causes cells to die by disrupting their integrity, causing microvascular and alveolar disruption.…”
Section: Discussionmentioning
confidence: 99%